2017
DOI: 10.1371/journal.pone.0179447
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of herpes zoster in patients with psoriasis: A population-based retrospective cohort study

Abstract: ObjectivesThe risk of herpes zoster (HZ) between patients with psoriasis receiving and not receiving systemic therapy has received increasing attention. This study investigated the association of psoriasis with the risk of HZ.MethodsWe conducted a population-based retrospective cohort study by using the Taiwan National Health Insurance Research Database. The psoriasis cohort consisted of 4077 patients with newly diagnosed psoriasis between 2000 and 2006. Each patient with psoriasis was frequency-matched with f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 38 publications
4
28
0
Order By: Relevance
“…A single-center retrospective study also showed that the risk of HZ was higher in younger patients who received liver transplantations, and this supports the need for vaccination among younger patients 23. A retrospective population-based study performed in Taiwan reported a high risk of HZ in patients with psoriasis who were aged between 20 and 39 years old 24. Taken together, these data indicate that younger patients with chronic inflammatory disorders that require systemic immunosuppressive therapy have a relatively higher risk than the general population of developing HZ.…”
Section: Discussionmentioning
confidence: 74%
“…A single-center retrospective study also showed that the risk of HZ was higher in younger patients who received liver transplantations, and this supports the need for vaccination among younger patients 23. A retrospective population-based study performed in Taiwan reported a high risk of HZ in patients with psoriasis who were aged between 20 and 39 years old 24. Taken together, these data indicate that younger patients with chronic inflammatory disorders that require systemic immunosuppressive therapy have a relatively higher risk than the general population of developing HZ.…”
Section: Discussionmentioning
confidence: 74%
“…Severe psoriasis was defined as patients receiving phototherapy (e.g., ultraviolet B (psoralen) and ultraviolet A) and/or immunomodulatory drugs (e.g., methotrexate, azathioprine, ciclosporin, oral retinoids, hydroxyurea, mycophenolate mofetil, tacrolimus, etanercept, adalimumab, and ustekinumab). Patients not receiving phototherapy and/or immunomodulatory drugs for psoriasis were classified as having mild psoriasis [12].…”
Section: Methodsmentioning
confidence: 99%
“…Differences in study setting and design will also impact estimates of other complications, as well as the costs associated with HZ. Some findings were unexpected, such as the observation in one study that the use of systemic steroids was strongly associated with a reduced risk of developing HZ [30]. This finding is difficult to interpret given that patients with psoriasis were likely to be receiving other immune-modulating drugs that may have influenced the risk of developing HZ.…”
Section: Discussionmentioning
confidence: 99%
“…The potential association was weaker in persons with depression, psychiatric disease, hyperlipidemia, hypertension, as well as those post-general anesthesia (range of HRs: 1.11-1.29) [20,25,26,28,29]. Conversely, systemic steroid use in patients with psoriasis was associated with a significantly reduced risk of HZ (HR: 0.6, 95% CI: 0.44-0.81) [30], as was radical prostatectomy and hormone therapy in patients with prostate cancer (HR: 0.60, 95% CI: 0.44-0.81) [31].…”
Section: The Risk Of Hz In Patients With Other Co-morbiditiesmentioning
confidence: 98%